Bidder Asymmetry in Infrastructure Procurement: Are There Any Fringe Bidders? - Estache, Antonio (2012)
Asymmetric auctions are among the most rapidly growing areas in the auction literature. The potential benefits from intensified auction competition could be enormous in the public procurement context. Entrant bidders are considered a key to enhance competition and break potential collusive arrangements among incumbent bidders. Asymmetric auction theory predicts that weak (fringe) bidders would bid more aggressively when they are faced with a strong (incumbent) opponent. Using data from official development projects, this paper shows that entrants actually submitted aggressive bids in the presence of incumbent(s) in the road sector and to a certain extent in the water sector. For electricity projects, the general competition effect is found to be particularly significant, but the entrant effect remains unclear. The results suggest that auctioneers should foster competition in public procurement, including fringe bidders, to contain public infrastructure investment costs.